2023
DOI: 10.1007/s11096-023-01636-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an online advanced suicide prevention training for pharmacists

Samantha Pilbrow,
Lexy Staniland,
Hannah V. Uren
et al.

Abstract: Background With the pharmacist role extending internationally to include health promotion and harm reduction, pharmacists are well-suited to adopt a frontline role within suicide prevention efforts. To maximise their abilities to implement suicide prevention strategies, suicide prevention training is essential to improve pharmacists’ knowledge of, attitudes towards, and confidence in pharmacy-based suicide prevention. Aim This study aimed to evaluate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…16 , 25 The reductions in ASP score reported are comparable to those seen with other pharmacy-based suicide prevention training evaluations such as Cates et al (pre: 33.1, (SD 4.3); post 30.0 (SD 6.6), p < 0.001) 16 Pilbrow et al reported improved attitudes and self-efficacy in suicide prevention immediately and 6 months after an online, synchronous suicide prevention training of pharmacists in Tasmania, Australia. 26 Witry et al 18 surveyed pharmacy students somewhere between 6 and 18 months after MHFA training and 44% had reported asking someone if they were thinking about suicide, although they did not report comparative pre-training data. However, it is difficult to understand the impact of such changes in scores, particularly as self-assessment has been shown to overestimate competence.…”
Section: Discussionmentioning
confidence: 99%
“…16 , 25 The reductions in ASP score reported are comparable to those seen with other pharmacy-based suicide prevention training evaluations such as Cates et al (pre: 33.1, (SD 4.3); post 30.0 (SD 6.6), p < 0.001) 16 Pilbrow et al reported improved attitudes and self-efficacy in suicide prevention immediately and 6 months after an online, synchronous suicide prevention training of pharmacists in Tasmania, Australia. 26 Witry et al 18 surveyed pharmacy students somewhere between 6 and 18 months after MHFA training and 44% had reported asking someone if they were thinking about suicide, although they did not report comparative pre-training data. However, it is difficult to understand the impact of such changes in scores, particularly as self-assessment has been shown to overestimate competence.…”
Section: Discussionmentioning
confidence: 99%